Recognition and management of COVID-19 and other influenza-like illnesses: a guide for paramedics. (2nd December 2021) - Tang, Sammer; Cowell, Sian
Abstract : During the pandemic last year, the incidence of influenza-like illnesses (ILIs) was significantly lower, as preventive measures aimed to reduce the spread of COVID-19, were also successful in preventing the spread of other respiratory illnesses. With relaxed COVID-19 measures and the return of social contact and mixing, a significant increase in ILIs is anticipated this winter. Common causative pathogens for ILIs include influenza viruses, parainfluenza virus, respiratory syncytial virus (RSV), rhinovirus and SARS-CoV-2. With similar characteristics and mode of transmissions, it may be difficult to distinguish between these common respiratory pathogens. Fortunately, the majority of ILIs are self-limiting and treatments for these illnesses are similar: supportive treatment to relieve symptoms while awaiting recovery. Paramedics should be aware of the warning signs of serious diseases and consider admission if they occur. Finally, good infection prevention and control measures are vital to break the chain of transmission of ILIs and protect yourselves and others from them.